Collaborative Writing Using Google Docs in an EFL Classroom: Voices from High School Students - Salim Nabhan; Halimatus Sa'diyah (Universitas Hamzanwadi, 2021)
The employment of technology in the teaching and learning process is unavoidable in the digital age. One of the online media utilized in English classes is Google Docs. However, there has been minimal discussion on the use of Google Docs for collaborative writing, particularly in high school EFL classes. As a result, the purpose of this study is to find out what EFL students think about utilizing Google Docs for collaborative writing in an English class at a senior high school. The researchers performed a qualitative case study to solve the problem. The information was gathered through an interview with kids from one of Sidoarjo's private schools in East Java, Indonesia. To support the main, classroom observations and the analysis of students' documents in the form of a portfolio were used to triangulate the data. After that, the data were subjected to thematic analysis. The study uncovered two key topics that addressed the advantages and drawbacks of utilizing Google Docs for collaborative writing. Students' enthusiasm, digital literacy, social skills, and writing skills improved when they used Google Docs for collaborative writing. Students, on the other hand, experienced some difficulties in terms of internet connection, the availability of accompanying gadgets, and their own abilities. The findings of the study could have practical implications in English classes.